Penerapan Teknologi Virtual Reality terhadap Perilaku Nyeri Pasien Pasca Bedah ORIF Fraktur Ekstremitas Bawah Saat Penggantian Balutan Luka - Robin Ferdiansyah Sitopu; Jenny Marlindawani Purba; Kiking Ritarwan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to identify the effect of applying virtual reality technology on pain behavior in postoperative ORIF patients with lower extremity fractures during dressing changes. The type of research used is a quasi-experimental nonequivalent control group pretest-posttest design. The sample in this study amounted to 50 patients after ORIF surgery for lower extremity fractures who underwent a wound dressing replacement procedure with a consecutive sampling technique. The research instrument consisted of a demographic data questionnaire, virtual reality devices and media and the Behavioral Pain Scale-Non Intubated (BPS-NI). The results showed that as many as 22 respondents (88%) who received virtual reality intervention when changing wound dressings did not show any pain, while the other 3 respondents experienced mild pain (12%). The results of the statistical test analysis Wilcoxon-Signed Ranked and Mann Whitney obtained a p-value <0.05. In conclusion, there is an effect of applying virtual reality technology in reducing pain as indicated by changes in pain behavior of patients after ORIF surgery for lower extremity fractures when changing wound dressings. Keywords: Change of Wound Bandage, Pain Behavior, Virtual Reality